Metabolites and Hypertension: Insights into Hypertension as a Metabolic Disorder. Issue 6 (June 2020) - Chakraborty, Saroj; Mandal, Juthika; Yang, Tao; Cheng, Xi; Yeo, Ji-Youn; McCarthy, Cameron G.; Wenceslau, Camilla F.; Koch, Lauren G.; Hill, Jennifer W.; Vijay-Kumar, Matam; Joe, Bina
Abstract : For over 100 years, essential hypertension has been researched from different perspectives ranging from genetics, physiology, and immunology to more recent ones encompassing microbiology (microbiota) as a previously underappreciated field of study contributing to the cause of hypertension. Each field of study in isolation has uniquely contributed to a variety of underlying mechanisms of blood pressure regulation. Even so, clinical management of essential hypertension has remained somewhat static. We, therefore, asked if there are any converging lines of evidence from these individual fields that could be amenable for a better clinical prognosis. Accordingly, here we present converging evidence which support the view that metabolic dysfunction underlies essential hypertension.